1984
DOI: 10.1007/bf02405353
|View full text |Cite
|
Sign up to set email alerts
|

Comparative radioautographic study of the effects of L-azetidine-2-carboxylic acid on matrix secretion and golgi of the mouse incisor

Abstract: The effect of a proline analog, L-azetidine-2-carboxylic acid (LACA), on protein matrix secretion by odontoblasts and ameloblasts was compared by light and electron microscopic radioautography after injection of 3H-glycine in young mice. LACA inhibited the secretion of dentin matrix with consequent accumulation of 3H-glycine labeled procollagen in the cisternae of the rough endoplasmic reticulum. In contrast, LACA had no apparent effect on ameloblasts as enamel matrix continued to be packaged in the Golgi appa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

1985
1985
1989
1989

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Quantitative analysis of silver grains in light microscopic radioautographs of 1-pm sections showed a pattern of 3H-glycine utilization in LACA-treated fibroblasts and osteoblasts similar to that observed in previous studies of collagen secretion in LACA-treated odontoblasts (Cho and Garant. 1984).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Quantitative analysis of silver grains in light microscopic radioautographs of 1-pm sections showed a pattern of 3H-glycine utilization in LACA-treated fibroblasts and osteoblasts similar to that observed in previous studies of collagen secretion in LACA-treated odontoblasts (Cho and Garant. 1984).…”
Section: Discussionsupporting
confidence: 82%
“…We have already shown that the structure of the Golgi apparatus of odontoblasts (collagen secretor) is affected by LACA administration while that of ameloblasts (noncollagenous protein secretor) remains unchanged (Cho and Garant, 1984). To further confirm the effect of LACA on the structure of the Golgi apparatus of other collagensecreting cells, we conducted a n electron microscopic and radioautographic study of collagen secretion in LACA-treated fibroblasts and osteoblasts.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…However, unlike in collagen secretion where the 3H-proline labelled precursors accumulate relatively close to the cell surface, the 3H-fucose labelled glycoproteins appear to spread more rapidly from the secretory pole of the cell. It is of interest that 3H-fucose labelled glycoproteins secreted by odontoblasts appear to migrate to the mineralization front within 4 hours while 3H-proline labelled collagen requires approximately one full day to reach the same site (Weinstock et al 1972, Cho & Garant 1984.…”
Section: Discussionmentioning
confidence: 99%
“…1972: Wein stock and Leblond. 1974: Cho and Garant. 1984, fibro blasts or odontoblasts form secretory granules that contain collagenous fibrillar material with various banding periods.…”
Section: Discussionmentioning
confidence: 99%